Molly of Denali. Molly and the great one [videorecording (DVD)] - Waugh, Kathy; Gillim, Dorothea (PBS Kids, 2021)
An action-adventure comedy that follows the adventures of feisty and resourceful ten-year-old Molly Mabray, an Alaska Native girl, her dog Suki, and friends Tooey and Trini on their adventures in epically beautiful Alaska.